A Bibliometric Analysis of Telemedicine: Remote Healthcare Delivery over the Years - Leena, Hima; Gochhait, Saikat (International Journal of Psychosocial Rehabilitation, 2020)
The concept of telemedicine plays a huge role in the digital evolution of healthcare. With the onset of social distancing and lockdowns, remote healthcare that allows efficient diagnosis and treatment using telecommunication devices plays a major part in our daily lifestyle (Gochhait & Omale, 2019). Over 70% of the healthcare industry uses telemedicine in the form of gadgets or apps to connect with their patients. The purpose of this paper is to analyze how much telemedicine has grown and its diverse applications and benefits in the field of healthcare and technology throughout the years by performing a bibliometric analysis of databases from the Web of Science Core Collection. Numerous records were analyzed, which talk about the various trends of telemedicine that have been used all around the world to improve healthcare and make it more available to us at anyplace and anytime.According to the analysis, the USA had the maximum number of publications on telemedicine, with Australia and England following. The years 2016-2019 showed the maximum publication, as these were the years when telemedicine and e-health devices and applications started to grow and become more popular.Telemedicine is now considered the answer to transform the healthcare business and improve patient care irrespective of where they are without compromising on their satisfaction. This analysis gives us an overview of the progress of e-health implemented around the world over the years (Gochhait & Omale, 2018).